Hubungan Rasa Kebersyukuran dengan Adversity Quotient pada Mahasiswa Penerima Beasiswa BIDIKMISI UIN Imam Bonjol - Sapni Alpionika; Murisal Murisal; Widia Sri Ardias (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
This research aimed to find out the level of gratification, the level of adversity quotient, and the relationship of gratitude with adversity quotient in UIN Imam Bonjol Padang BIDIKMISI recipient students. This research uses quantitative methods with data analysis techniques namely Pearson correlation analysis which the SPSS program version 20.0 for windows. The independent variable in this study is gratification and the dependent variable is the adversity quotient. Research subjects numbered 229 students receiving the bidikmisi UIN Imam Bonjol Padang. Data collection techniques used in this study are psychological scales, namely the scale of gratitude that the authors arrange themselves with a validity of 48 out of 60 items and have a reliability of 0,934 and an adversity quotient scale that the authors compose themselves with a validity of 50 out of 59 items and a reliability of 0,921. Based on the results of the analysis of research data shows the Pearson Correlation coefficient of 0,501 with a significance of 0,000 (0,000 < 0,05), so that it can be concluded that there is a significant relationship between gratification with adversity quotient in students receiving Bidikmisi State Islamic University (UIN) Imam Bonjol Padang. These results also indicate that bidikmisi recipient students have average scores of high gratification rates and moderate dominant adversity quotient levels.